The New Lombard street : how the fed became the dealer of last resort - Mehrling, Perry G., 1959- (Princeton University Press, 2010)
Walter Bagehot's Lombard Street, published in 1873 in the wake of a devastating London bank collapse, explained in clear and straightforward terms why central banks must serve as the lender of last resort to ensure liquidity in a faltering credit system. Bagehot's book set down the principles that helped define the role of modern central banks, particularly in times of crisis--but the recent global financial meltdown has posed unforeseen challenges. The New Lombard Street lays out the innovative principles needed to address the instability of today's markets and to rebuild our financial system. Revealing how we arrived at the current crisis, Perry Mehrling traces the evolution of ideas and institutions in the American banking system since the establishment of the Federal Reserve in 1913. He explains how the Fed took classic central banking wisdom from Britain and Europe and adapted it to America's unique and considerably more volatile financial conditions. Mehrling demonstrates how the Fed increasingly found itself serving as the dealer of last resort to ensure the liquidity of securities markets--most dramatically amid the recent financial crisis. Now, as fallout from the crisis forces the Fed to adapt in unprecedented ways, new principles are needed to guide it. In The New Lombard Street, Mehrling persuasively argues for a return to the classic central bankers' "money view," which looks to the money market to assess risk and restore faith in our financial system.